2022
DOI: 10.3389/fneur.2022.913193
|View full text |Cite
|
Sign up to set email alerts
|

Effects of 3-month CPAP therapy on brain structure in obstructive sleep apnea: A diffusion tensor imaging study

Abstract: White matter (WM) fiber alterations in patients with obstructive sleep apnea (OSA) is associated with cognitive impairment, which can be alleviated by continuous positive airway pressure (CPAP). In this study, we aimed to investigate the changes in WM in patients with OSA at baseline (pre-CPAP) and 3 months after CPAP adherence treatment (post-CPAP), and to provide a basis for understanding the reversible changes after WM alteration in this disease. Magnetic resonance imaging (MRI) was performed on 20 severely… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 54 publications
0
10
0
1
Order By: Relevance
“…The morphologically detectable changes are partially reversible by successful PAP therapy 66 121 122 123 . The irreversible morphologic brain changes are associated with residual daytime sleepiness despite adequate therapy 64 78 124 .…”
Section: Obstructive Sleep Apnea Syndrome and Cognitionmentioning
confidence: 99%
See 1 more Smart Citation
“…The morphologically detectable changes are partially reversible by successful PAP therapy 66 121 122 123 . The irreversible morphologic brain changes are associated with residual daytime sleepiness despite adequate therapy 64 78 124 .…”
Section: Obstructive Sleep Apnea Syndrome and Cognitionmentioning
confidence: 99%
“…Die morphologisch nachweisbaren VerĂ€nderungen sind teilweise durch eine erfolgreiche PAP-Therapie reversibel 66 121 122 123 . Die irreversiblen morphologischen HirnverĂ€nderungen werden mit einer residuellen TagesschlĂ€frigkeit trotz ausreichender Therapie in Verbindung gebracht 64 78 124 .…”
Section: 41 Pap-therapieunclassified
“…30 However, we did not observe similar results in our previous study, including no reversible restoration of WM fiber bundle integrity in patients with OSA after short-term (three months) CPAP treatment. 31 Moreover, few studies have investigated whether the structure of WM fiber tracts is reversed after long-term CPAP treatment.…”
Section: Introductionmentioning
confidence: 99%
“…A diffusion tensor imaging study found almost complete recovery from white matter abnormalities in OSA patients after 12 months of CPAP treatment [ 29 ]. Our previous resting-state functional magnetic resonance imaging (rs-fMRI) study found that after 1 month of CPAP treatment, spontaneous brain activity in the bilateral cerebellum posterior lobe, right superior frontal gyrus (SFG), and left precentral gyrus could reverse, and these changes were associated with improvements in cognition and sleepiness, but no structural brain changes were found, suggesting that functional changes may be asynchronous with structural changes [ 30 , 31 ]. However, no study on the FC of insular subregions after CPAP treatment in OSA patients has been reported.…”
Section: Introductionmentioning
confidence: 99%